GAMBARAN WANITA DEWASA AWAL YANG MENGALAMI FATHERLESS - Turyati, Tri Vaiqotusa'adah; Setyo Ariyanto, Mustaqim (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Indonesia ranks third in the world for cases of fatherlessness. Fatherlessness refers to a condition in which a person's development lacks the psychological and physiological role of a father. This condition is important to study because it can affect an individual's psychological well-being, especially in early adulthood. This study aims to describe the aspects of fatherlessness and identify the factors that influence it. The research method used is a qualitative phenomenological approach, with two early adult women as subjects, one due to a broken home and the other due to the death of their father. Data were collected through in-depth interviews, unstructured observations, and documentation, which were then analyzed descriptively. The results of the study show that both subjects did not receive optimal father roles in various aspects, leading to negative impacts such as feelings of sadness, anger, envy, low self-esteem, and emotional trauma. In conclusion, fatherlessness has a significant impact on the psychological well-being of early adult women, particularly in emotional and social aspects. The implications of this study emphasize the importance of the father's role in the family as a psychological foundation for children. ABSTRAK Indonesia menempati urutan ketiga di dunia untuk kasus